Freud : the unconscious and world affairs - Major, Rene (Routledge, 2018)
This book sheds a new light on Freud who, from the beginning, was aware that the edifice he was constructing – psychoanalysis – which revealed in each individual an "ego not master in its own house" –, had clear implications for understanding collective human behaviour. This man was profoundly concerned with matters of peace and war, religion, morality and civilisation.